Analisis Transmisi Harga Jagung sebagai Bahan Pakan Ternak Ayam Ras di Sumatera Barat - E Rahmi; B Arif (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2012)
The reseacrh was conducted in West Pasaman West Sumatera. There was a phenomenon in the research area that poultry farmers had difficulty to get maize for layer feed and the tendency of price increase of maize after the operation of feed industry. The purpose of the reseacrh were to analyze the elasticity of price transmission between producers and consumers pricing. Method of the research was a quantitative description and statistic analyze to measure elasticity of price transmission between producers and consumers pricing. Data used in the research was secondary data. The result of research revealed that elasticity of price transmission was small (η = 0,26), indicated that the price change at farmer level was lower than consumers level therefore the market of maize in West Sumatera was not efficient.